Advanced lightweight steel floor towards high sound insulation and fire resistance. (June 2020) - Terrados-Cepeda, F. Javier; Lizana, Jesus
Abstract: Industrialized lightweight buildings have great advantages associated with lower indirect costs, minimum construction wastes and faster construction processes. However, their main weaknesses lie in their acoustic performance and fire resistance. This paper develops and assesses a novel lightweight steel floor with high fire resistance and high acoustic performance for buildings. Acoustic measurements through laboratory tests were carried out according to ISO 10140:2010 and ISO 717:2013. Fire resistance was tested according to EN 1365–2:2000. The results demonstrate that using an appropriate structural and resilient layer through an optimized design, insulating the floor surface from the surrounding structure, separating structural systems between layers, minimizing flanking transmissions through resilient strips and joint sealing between boards, a Weighted sound reduction index of Rw (C; Ctr ) ≥ 65 (−6; −14) dB, and a Weighted normalized impact sound pressure level of Ln, w (CI ) ≤ 49, 9 (4) dB can be achieved, along with a fire resistance of REI45. Highlights: Development of an advanced lightweight steel floor system. Assessment of airborne and impact insulation and fire resistance. Acoustic and fire measurements through laboratory tests. Characterisation and comparison with previous assemblies. High acoustic performance and fire resistance.